Acute mental health nursing : from acute concerns to the capable practitioner - Harrison, Marc; Howard, David, RGN; Mitchell, Damian (SAGE Publications, 2004)
Recent mental health policy has focused on developing community-based services, while the reality remains that patients experiencing acute episodes of illness are mainly cared for in hospital. Acute Mental Health Nursing has been developed as a guide to the core knowledge and skills required for working in inpatient settings.